2014
DOI: 10.1186/s13048-014-0084-4
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA 490-3P enhances the drug-resistance of human ovarian cancer cells

Abstract: BackgroundMicroRNAs (miRNAs) are non-coding, single-stranded small RNAs that regulate gene expression negatively, which is involved in fundamental cellular processes. In this study, we investigated the role of miR-490-3P in the development of drug resistance in ovarian cancer cells.MethodsThe human ovarian carcinoma cell line A2780 and A2780/Taxol were exposed to paclitaxel in the presence or absence of microRNA 490-3P transfection, after which cell viability were performed by CCK-8 assay. Reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…A deeper insight into the molecular mechanism of drug resistance is the key to resolving the issue. Several researchers have proved that expression dysregulation of miRNA in tumor cells could influence their sensitivity of the tumor to drugs by regulating target gene expression 2022. Therefore, target-regulating miRNA is the advanced pathway for overcoming chemotherapy resistance of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper insight into the molecular mechanism of drug resistance is the key to resolving the issue. Several researchers have proved that expression dysregulation of miRNA in tumor cells could influence their sensitivity of the tumor to drugs by regulating target gene expression 2022. Therefore, target-regulating miRNA is the advanced pathway for overcoming chemotherapy resistance of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the role of Hsa-miR-490 as potential drug resistance in ovarian cancer [147] and as a potential novel biomarker for diagnosing of colorectal cancer [148]. …”
Section: Discussionmentioning
confidence: 99%
“…miRNA treatment includes miRNA that substitutes low expression and miRNA that inhibits overexpression. Previous studies have used agomirs and antagomirs as analogues and inhibitors, respectively, of miRNAs for the treatment of cancer, and a large number of experiments in vivo have been conducted (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%